PENGGUNAAN MEDIA VISUAL PEMBELAJARAN SEJARAH BERBASIS LINGKUNGAN LOKAL - Meyliana; Anggini, Reva; Rena; Susilo, Agus (Journal of Language Teaching Lingustics and Literature, 2024)
This study aims to develop and implement local environment-based visual media in history learning. The visual media developed is expected to improve students' understanding of historical materials in a more interesting and contextual way. In writing this scientific paper, the author uses literature studies and uses reference sources through books or journals that are relevant to the topics discussed. The results of the study indicate that the use of local environment-based visual media is quite effective in increasing students' motivation and understanding of historical materials. This media also helps students relate subject matter to their surroundings, so that learning becomes more relevant and meaningful. Thus, the use of local environment-based visual media can be an effective alternative in history learning in schools.